Through Narcissus' Glass Darkly : The Modern Religion of Conscience - Cahill, Kevin M. (Book collections on Project MUSE., 2005)
For more than forty-five years, Kevin Cahill has been helping to heal the world: as a leading specialist in tropical medicine and as a driving force in humanitarian assistance and relief efforts across the globe. Physician, teacher, activist, diplomat, and advocate, Cahill has touched many lives and helped right many wrongs. In this book, he chronicles extraordinary achievements of compassion and commitment. Bringing together a rich selection of writings?essays, op-ed pieces, speeches, and other works, many out of print or hard to find?he crafts a fascinating self-portrait of a life devoted to.